Treatment patterns, risk for hospitalization and mortality in older patients with triple negative breast cancer. Issue 2 (March 2021) - Valachis, Antonis; Nyström, Pontus; Fredriksson, Irma; Wennstig, Anna-Karin; Ahlgren, Johan
Abstract: Objectives: To study the treatment patterns, potential risk factors for hospitalization within one year from diagnosis, and causes of death in older patients with triple negative breast cancer (TNBC). Materials and Methods: We performed a registry-based cohort study using the BCBaSe database which links cases of breast cancer from three Swedish healthcare regions with socioeconomic factors, hospitalizations and causes of death. Women ≥70 years old with non-metastatic TNBC, between 1/12007 and 31/122012 were included ( n = 413). Results: In total, 168 patients (40.7%) received chemotherapy after surgery and 123 patients (30.0%) in the whole cohort had at least one hospitalization within one year from diagnosis. The risk of hospitalization overall was increased in the group receiving chemotherapy (Odds Ratio 2.35, 95% Confidence Intervall: 1.30–4.26) mainly due to toxicities. Cumulative incidence of breast cancer mortality was comparable among different age groups (70–74 vs. 75–79 vs. ≥ 80 years old) whereas non-breast cancer mortality was higher in patients ≥80 years old. Stage at diagnosis and comorbidities were independently associated with both breast cancer-specific- and overall mortality whereas age was only associated with overall mortality. Conclusions: The use of chemotherapy in older patients with TNBC was associated with age, tumor stage, and comorbidities. Chemotherapy use was also associated with increased risk for hospitalization within one year from diagnosis. Although the impact of chemotherapy on mortality was analyzed in a multivariate manner showing neither increased or decreased mortality, no firm conclusion can be drawn due to unmeasured confounders.